The Cochrane database of systematic reviews
A collection of regularly updated, systematic reviews of the effects of health care. New reviews are added with each issue of The Cochrane Library. Reviews mainly of randomised controlled trials. Evidence is included or excluded on the basis of explicit quality criteria to minimise bias. Data are often combined statistically, with meta-analysis, to increase the power of the findings of numerous studies each too small to produce reliable results individually.
Keywords: Medicine : Research : Statistical methods; Evidence-based medicine : Periodicals : Databases; Clinical trials : Periodicals : Databases; Systematic reviews (Medical research) : Periodicals : Databases; Research; Evidence-Based Medicine; Randomized Controlled Trials as Topic; Research Design; Clinical trials; Evidence-based medicine; Systematic reviews (Medical research); Medical Ethics & Philosophy